Characteristic People With Hypertension in Yogyakarta Special Region During The First Year of Covid-19 Pandemics - Rokhmayanti Rokhmayanti; Sulistyawati Sulistyawati; Budi Aji; Siwi Pramatama Mars Wijayanti; Ummul Khair (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Since 2017, hypertension was the top first disease in the Yogyakarta Special Region (DIY). It cannot be ignored because hypertension is an entrance for other degenerative diseases. Along with the COVID-19 pandemic at the beginning of 2020 raising our curiosity whether there has been a change in the incidence of hypertension in DIY during this year, then what are its characteristics. This study explores the characteristics of people with hypertension by age group and gender in the first year of the COVID-19 pandemic in the Yogyakarta Special Region. A descriptive study was employed in this study, with the main source was the secondary data from the Yogyakarta Special Region health office, the year 2020. Analysis was conducted by univariate tabulation. Data from the Yogyakarta provincial health office shows that in 2020 there will be an increase of more than eight thousand cases of hypertension. In general, this increase was lower than the increase in the previous two years. In 2020, the highest incidence of hypertension was found in women in the age range of 60-69. Meanwhile, in the (15–19) age group, the majority of cases happened in men. This study shows that during 2020, which was the COVID-19 pandemic, the incidence of hypertension increased but not as high as the previous two years. The majority of hypertension occurred in the 60-69 age group, with the majority in men.